Modelling and measurements of thermally induced residual stress in IN718 nickel-based superalloy during non-uniform quenching - S. Rahimi; M. King; M. Amir Siddiq; B.P. Wynne (Materials & Design)
Residual stress induced during and as a result of manufacturing processes can have a significant impact on the later stages of manufacturing (e.g., machining), and in-service performance (e.g., resistance to fatigue) of a component. In this work, a novel approach is presented by combining FE based residual stress predictions with experimental verification at scales comparable to industrial components, which is rarely reported. Instrumented plates of IN718 nickel-based superalloys have been water-quenched and air-cooled from solution annealing temperature (980 °C) and the associated cooling curves were measured at specified locations. The cooling curves were used as boundary conditions for inverse calculation of zone-specific heat transfer coefficient (HTC), which is the main parameter to estimate the heat exchange rate between different regions of a heated part and its surrounding environment. The HTCs have then been implemented in an elastic–plastic finite-element model, which included temperature dependant thermo-mechanical properties to predict thermally induced residual stress fields during heterogeneous water/air quenching from. For the verification of the model, identical plates were heterogeneously quenched (half in water and half in air) from 980 °C, both vertically and horizontally, and residual stress was then measured in both plates using the contour method and incremental central hole drilling.